Pengaruh Performance Exterior dan Tingkat Kegemukan Sebagai Penentu Harga Taksir Sapi Bali Jantan Di Kecamatan Awangpone Kabupaten Bone: The Effect of Exterior Performance and Fatness Level as Determinantsof the Estimated Price of Male Bali Cattle in Awangpone Subdistrict, Bone Regency - Ainun Aliyah; Muhammad Basir Paly; Rusny Rusny (Universitas Islam Negeri Alauddin Makassar, 2023)
The selling price of beef cattle is usually influenced by the appearance of the cow. This is generally called